Flow‐Induced Precipitation in Thin Capillaries Creates Helices, Lamellae, and Tubes. Issue 61 (9th October 2019) - Knoll, Pamela; Gonzalez, Alexander V.; McQueen, Zachary C.; Steinbock, Oliver
Abstract: Precipitation reactions under flow in confined media are relevant to the control of pathological biomineralization, processes affecting aquifers, and challenges in the petroleum industry. Here we show that for a simple geometry, such conditions create macroscopic structures including helices, tubes, lamellae, slugs, and disordered patterns. All structures emerge when salt solution is slowly injected into thin capillaries filled with hydroxide solution. For the helices, the pitch is proportional to the pump rate revealing a constant period of 0.63 s. Different morphologies of the insoluble metal hydroxide can co‐exist causing random transitions along the capillary. On average, 15 % of the final system contains residual hydroxide solution. While mechanically stable for flow speeds above 25 mm min −1, structures collapse and sediment for slower injection speeds. Some of the observed features share similarities with precipitate tubes in chemical gardens and the dynamics of liquid–liquid pipe flow. Abstract : Making helical structures is as easy as displacing NaOH with metal salt solutions. This process also creates lamella‐like precipitates that show shear‐induced periodic ripples and tube structures that are reminiscent of chemical gardens. The helix pitch and final volume fractions are proportional to the injection rate.